2007
DOI: 10.1248/bpb.30.313
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus (FK506) Limits Accumulation of Granulocytes and Platelets and Protects against Brain Damage after Transient Focal Cerebral Ischemia in Rat

Abstract: Cerebral ischemia is one of the most frequent causes of disability and death in later life. The primary aim of therapeutic intervention for cerebral ischemia is to reduce the volume of brain damage and thus to minimize the neurological impairment. Because neuronal degeneration after cerebral ischemia can progress rapidly and is often irreversible, the benefit of effective pharmacological intervention is quite limited at present. The only medication proven to be effective and widely used at the acute stage of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
(27 reference statements)
3
11
0
Order By: Relevance
“…Immunoreactivity for pimonidazole was characterized by three different patterns of distribution [65]: firstly, we observed a diffuse immunostaining in various cerebral regions, including the hippocampus (Fig. 3B), similar to that reported in the penumbra of cerebral ischemic lesions in rat models [59][60][61]; secondly, we found previously unreported Golgi-like stained cells in various hippocampal and extrahippocampal regions; and thirdly, darkly stained neuronal somas were detected in specific brain regions, resembling the distribution described in a model of cerebral malaria [66]. Notably, pimonidazole-immunopositive cells increased and became more widespread by prolonging the duration of SE.…”
Section: Evidence For Exposure To Hypoxia During Se Is Provided By Adsupporting
confidence: 83%
See 2 more Smart Citations
“…Immunoreactivity for pimonidazole was characterized by three different patterns of distribution [65]: firstly, we observed a diffuse immunostaining in various cerebral regions, including the hippocampus (Fig. 3B), similar to that reported in the penumbra of cerebral ischemic lesions in rat models [59][60][61]; secondly, we found previously unreported Golgi-like stained cells in various hippocampal and extrahippocampal regions; and thirdly, darkly stained neuronal somas were detected in specific brain regions, resembling the distribution described in a model of cerebral malaria [66]. Notably, pimonidazole-immunopositive cells increased and became more widespread by prolonging the duration of SE.…”
Section: Evidence For Exposure To Hypoxia During Se Is Provided By Adsupporting
confidence: 83%
“…Note the presence of a diffuse immunoprecipitate around the lesion core (arrows); this latter was not reached by pimonidazole probably because of limited blood flow. The pattern of immunostaining was similar to that which is known to occur in regions of cerebral ischemia [59][60][61]. C, immunoreactivity for hypoxia-inducible factor 1α (HIF-1α) [65] was found to be intense around the lesion core (arrows).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…However, lowering platelet numbers in patients with cancer requires careful titration, as thrombocytopenia can easily lead to life-threatening bleeding complications. Although platelet function and numbers can change under hypoxic conditions (27)(28)(29)55), their role in tumor hypoxia, especially with regard to antiangiogenic therapy-induced hypoxia, is not well understood. We showed that increased platelet infiltration after withdrawal of antiangiogenic therapy was dependent on expression of FAK in platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies have also shown that hypothermia or transductive anti-death FNK protein in combination with FK506 enhances neuroprotection against brain damage with focal transient ischemia in rats, the two treatments acting additively or synergistically against ischemic damage (Nito et al, 2004;Katsura et al, 2008). Although the precise mechanism producing the neuroprotective effects of FK506 is still unclear, previous studies have shown that FK506 exerts anti-apoptotic and anti-inflammatory effects on cerebral ischemic injury (Furuichi et al, 2004;Noto et al, 2007). Taking into account the extra-neurogenic effect of MSCs, we speculate that FK506 may act additively or synergistically with MSC transplantation.…”
Section: Introductionmentioning
confidence: 98%